The impact of resistance exercise range of motion on the magnitude of upper-body post-activation performance enhancement - Michał Krzysztofik; Robert Trybulski; Bartosz Trąbka; Dawid Perenc; Konrad Łuszcz; Adam Zajac; Dan Iulian Alexe; Tatiana Dobrescu; Cristina Elena Moraru (BMC, 2022)
Abstract Background Various studies have used different exercise protocols as post-activation performance enhancement (PAPE) stimulus; however, little attention has been given to the effects of exercise range of motion on the PAPE effect and subsequent performance enhancement. This study aimed to compare the PAPE responses induced by the bench press performed with different ranges of motion on subsequent bench press throw performance. Methods Ten resistance-trained males (age: 26 ± 3 years; body mass: 93.2 ± 9.4 kg; height: 181 ± 6 cm; experience in resistance training: 6.3 ± 2.4 years; relative bench press one-repetition maximum (1RM) 1.54 ± 0.2 kg/body mass) performed four experimental sessions consisting of a single set of the bench press at 80%1RM until mean barbell velocity dropped by 10% as the conditioning activity (CA) with a (1) standard, (2) cambered, (3) and reversed cambered barbell or a control condition in which the participants did not perform any CA. To assess the PAPE effect, single-sets of 2 repetitions of the bench press throw at 30%1RM were performed before and after the CA at the following time points: 2, 4, 6, 8, 10 min. Results The two-way ANOVA (4 conditions × 2time points) showed a significant interaction for peak power (p < 0.001; η2 = 0.556) and peak velocity (p = 0.001; η2 = 0.457). The standard barbell bench press CA led to the greatest performance enhancement in peak power (p = 0.001; ES = 0.54) and in peak velocity (p = 0.002; ES = 0.71) within the examined conditions. Conclusions The results of this study indicate that the range of motion of the CA has a significant impact on the magnitude of the PAPE response, and the greatest effect can be reached when the range of motion of the CA and the subsequent explosive task is similar.